PENGEMBANGAN POTENSI WISATA DI DESA WISATA SIDOREJO KECAMATAN LENDAH KABUPATEN KULON PROGO - Pangky Arbindarta Kusuma; Yerika Ayu Salindri (STIE Pariwisata API Yogyakarta, 2022)
The objective of this research is to identify the potential attraction of the Sidorejo Tourism Village located in Lendah District, Kulon Progo Regency. In identifying, the researchers used several methods both in collecting data and processing data. Steps to collect data include FGD, interviews, observations, library studies and documentation, while the primary and secondary data processing obtained was carried out by descriptive-qualitative analysis, interpretation and analysis of tourism potential. It is resulted that Sidorejo Tourism Village has a various attractions including natural, cultural and artificial attractions. It is known that there are several problems in management and become quite influential obstacles related to the structure of management, management, education level and packaging of tourism products.